Relationship of Exo-β-d-Galactofuranosidase Kinetic Parameters to the Number of Phosphodiesters in Penicillium fellutanum Peptidophosphogalactomannan: Enzyme Purification and Kinetics of Glycopeptide and Galactofuran Chain Hydrolysis - Tuekam, Brigitte A. (American Society for Microbiology, 2001)
Extracellular Penicillium fellutanum exo-β-d-galactofuranosidase, with a mass of 70 kDa, was purified to apparent homogeneity. The enzyme was used to investigate the influence of phosphodiesters of the peptidophosphogalactomannans pP(2)GM(ii) and pP(25)GM(ii) (containing 2 and 25 phosphodiester residues, respectively, per mol of polymer) on the kinetic parameters of galactofuranosyl hydrolysis of these two polymers, of 1-O-methyl-β-d-galactofuranoside, and of two galactofuranooligosaccharides. The enzyme did not hydrolyze phosphorylated galactose residues of pP(2)GM(ii) or pP(25)GM(ii). The k(cat)/K(m) value for pP(25)GM(ii) is 1.7 × 10(3) M(−1) s(−1), that for 1-O-methyl-β-d-galactofuranoside is 1.1 × 10(4) M(−1) s(−1), that for pP(2)GM(ii) is 1.7 × 10 (4) M(−1) s(−1), and those for 5-O-β-d-galactofuranooligosaccharides with degrees of polymerization of 3.4 and 5.5 are 1.7 × 10(5) and 4.1 × 10(5) M(−1) s(−1), respectively. Variability in the k(cat)/K(m) values is due primarily to differences in K(m) values; the k(−1)/k(1) ratio likely provides the most influence on K(m). k(cat) increases as the degree of polymerization of galactofuranosyl residues increases. Most of the galactofuranosyl and phosphocholine residues were removed by day 8 in vivo from pP(x)GM(ii) added to day 3 cultures initiated in medium containing 2 mM phosphate but not from those initially containing 20 mM phosphate. The filtrates from day 9 cultures initiated in 2 mM inorganic phosphate in modified Raulin-Thom medium contained 0.2 mM inorganic phosphate and 2.2 U of galactofuranosidase ml(−1)h(−1). No galactofuranosidase activity but 15 mM inorganic phosphate was found in filtrates from day 9 cultures initiated in 20 mM phosphate. In vivo the rate of galactofuranosyl hydrolysis of pP(x)GM(ii) and of related polymers is proportional to the k(cat)/K(m) value of each polymer. The kinetic data show that the k(cat)/K(m) value increases as the number of phosphodiesters of pP(x)GM(ii) decreases, also resulting in an increase in the activity of exo-β-d-galactofuranosidase.